Inspiring and Informing Citizens Online: A Media Richness Analysis of Varied Civic Education Modalities. Issue 5 (5th June 2015) - Brinker, David L.; Gastil, John; Richards, Robert C.
Abstract: Public deliberation on the Internet is a promising but unproven practice. Online deliberation can engage large numbers of citizens at relatively low cost, but it is unclear whether such programs have substantial civic impact. One factor in determining their effectiveness may be the communicative features of the online setting in which they occur. Within a Media Richness Theory framework, we conducted a quasiexperiment to assess the civic outcomes of interventions executed online by nonprofit organizations prior to the 2012 U.S. presidential election. The results assess the impact of these interventions on issue knowledge and civic attitudes. Comparisons of the interventions illustrate the importance of considering media richness online, and our discussion considers the theoretical and practical implications of these findings.